Analysis of 4P Marketing Strategy at Yonna Cake Shop in Sukadana, East Lampung - Vera Agustina; Robi Santoso; Dina Nadiyah Faiqoh; Diki Angga Hendrawan (Indonesian Journal of Entrepreneurship and Startups, 2026)
This study aims to analyze the marketing strategy implemented by Toko Kue Yonna, a culinary micro, small, and medium enterprise (MSME) located in Sukadana, East Lampung Regency, using the 4P marketing mix framework (product, price, place, and promotion), and to examine how the implementation of this strategy supports the improvement of business sales. A qualitative method with a case study approach was employed. The primary informant was the business owner, selected through purposive sampling, and the data were strengthened through direct observation and documentation. Data were collected through semistructured interviews, field observation, and documentation, and were analyzed using the interactive model of Miles and Huberman. The results indicate that Toko Kue Yonna has implemented all four elements of the marketing mix in an integrated manner, and that this integration has contributed to a consistent increase in daily revenue, an expanding customer base, and business growth from a home-based operation into a physical store with ten personnel. The study concludes that a well-integrated 4P marketing mix strategy plays a significant role in supporting the sales growth and competitiveness of culinary MSMEs